Pengaruh Penyuluhan Kesehatan terhadap Tingkat Pengetahuan Program Jaminan Persalinan di Wilayah Kerja Puskesmas Sedayu 1 Kabupaten Bantul - Vidi Aditya Pamori Wibowo Putra; Rifai Hartanto; Endang Sutisna Sulaeman (Nexus Kedokteran Komunitas, 2014)
Background: Mass Labor Assurance (known as Jampersal) is a new program, it caused lack of knowledge in the peoples society from rural area. Based on data from Bantul Regency Health Department in 2011 there were 8,5 infant mortality per 1000 birth, and maternal mortality rate was 111,2 per 100.000 birth. Maternal mortality rate in Bantul Regencyincreased 29,1 per 100.000 birth compared with maternal mortality rate in 2010, while labor woman mortality rate was 82,1 per 100.000 birth (Bantul Regency Statistic Department, 2010). It was interesting, because on January 1st 2011 Mass Labor Assurance or Jampersal began to be implemented in every Indonesia region, meanwhile maternal mortality rate in Sedayu District of Bantul Regencyincreased. Methods: This research wasusing quasi experimental with pretest and posttestcontrol group design approaching study. Samplesin this researchwere mothers from Puskesmas Sedayu 1 of Bantul Regency working area. Samples were taken with rule of thumbs, divided by 2 groups consist of control group and treatment group.Total samples were 100 mothers, divided into control group and treatment group. The data was collected by quesioner test before and after the counseling Results: The knowledge difference about Jampersal in treatment and control group is count 14.94 with significant level 0.000 (p<0.05). Conclusion: Counselingwas increasing the mothers knowledge level about Mass Labor Assurance (Jampersal) programs. Keywords: counseling, knowledge, labor assurance